2004
DOI: 10.1074/jbc.m308391200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factors HIF-1 and HNF-4 and the Coactivator p300 Are Involved in Insulin-regulated Glucokinase Gene Expression via the Phosphatidylinositol 3-Kinase/Protein Kinase B Pathway

Abstract: Glucokinase plays a key role in the regulation of glucose utilization in liver and its expression is strongly enhanced by insulin and modulated by venous pO 2 . In primary rat hepatocytes, pO 2 modulated insulindependent glucokinase (GK) gene expression was abolished by wortmannin an inhibitor of phosphatidylinositol 3-kinase (PI3K). Transfection of vectors encoding the p110 catalytic subunit of PI3K or constitutively active proteinkinase B (PKB) stimulated GK mRNA and protein expression. The transfection of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 65 publications
2
82
1
1
Order By: Relevance
“…53 Many of these genes lead to increased glucose uptake [54][55][56] and glycolysis. 57 In this context HIF1A, by activating the expression of numerous glycolysis-related genes, as well as by increasing the expression of proteins that help cells capture blood glucose, is an inducer of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…53 Many of these genes lead to increased glucose uptake [54][55][56] and glycolysis. 57 In this context HIF1A, by activating the expression of numerous glycolysis-related genes, as well as by increasing the expression of proteins that help cells capture blood glucose, is an inducer of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the difference in modes of action of wortmannin in mammals and plants may relate to the more complicated role that the TGN/PCR plays in plant cells. Despite the many caveats in working with wortmannin (Roth et al, 2004), which also probably apply to plants, it will be interesting to determine whether the effects of wortmannin as described here in tobacco BY-2 cells can be confirmed in other plant cells. Indeed, an endosome as defined by labeling with At SNX1-GFP in Arabidopsis cells was recently shown to form small vacuoles in response to wortmannin treatment (Jaillais et al, 2006).…”
Section: Wortmannin Targets Both Early and Late Endosomes (Pvc) In Tomentioning
confidence: 99%
“…It would seem that whereas the internalization of PM receptors continues, or may even be increased, in the presence of wortmannin, receptor recycling or the further transport of receptors down the degradative pathway is inhibited (Roth et al, 2004). In addition to being present on multivesicular late endosomes, the substrate for PI-3K, PI3P, is also found on early endosomes (Rubino et al, 2000).…”
Section: Wortmannin Targets Both Early and Late Endosomes (Pvc) In Tomentioning
confidence: 99%
“…by modulating the function of FoxO1 and its interaction with HNF-4). Previously, we reported that HNF-4 plays an important role in stimulating the FoxO1 Regulates Glucokinase expression of GK in the liver and that an HNF-4 binding site in the proximal GK promoter is required for this effect (9). Previous studies also have shown that interaction between FoxO1 and HNF-4 disturbs HNF-4 function both by impairing its ability to bind to HNF-4 response elements (14) and by disrupting the function of the HNF-4 transactivation domain (64).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that several transcription factors, including USF-1 and -2 (upstream stimulatory factor-1 and -2) (7,8), HIF-1 (hypoxia-inducible factor-1) (9), PPAR␥ (peroxisome proliferator-activated receptor-␥) (10), sterol regulatory element binding protein-1c (11,12), and hepatocyte nuclear factor-4␣ (HNF-4␣) (13) may contribute to liver GK expression. We have reported that HNF-4 contributes to the effect of insulin on GK induction through a phosphatidylinositol 3Ј-kinase/protein kinase B-dependent mechanism (9). HNF-4 has been shown to interact with FoxO1 (14), an insulin-responsive transcription factor (15), suggesting the possibility that interactions between FoxO1 and HNF-4 may contribute to the regulation of GK expression.…”
mentioning
confidence: 98%